Pengesanan proses pengaratan dan perubahan PH dalam konkrit bertetulang menggunakan serabut optik - Erica Dina, Erica Dina (2006)
Corrosion of reinforcement is the major cause of the deterioration of reinforced concrete structure. Corroded reinforcement induces stresses in concrete cover that leads to cracking and spalling of concrete cover and finally results in the failure of the structure to carry the design loads. The main causes of reinforcement corrosion are carbonation and chloride ions attack. Acid and sulphate attack can also weaken the concrete. The objectives of this research were to look at the possibility of using fibre optic sensors to monitor the corrosion of reinforcement and to detect changes in pH of concrete and mortar. Both sensors used Plastic Clad Silica (PCS) optical fibres which were unclad, 4 cm long, at the centre portion. The light was made incidence to one end of the optical fibre and detected at the other end. For the corrosion sensor, unclad PCS optical fibre was attached to the reinforcement. The formation of rust on the reinforcement surface causes light to be refracted from fibre optic. Consequently, the intensity of light detected at the other end of the fibre was reduced. For the pH sensor, the unclad portion of optical fibre was dip coated in the silica sol-gel film. The color of the silica sol-gel film on fibre optic surface changes as the pH of solution and pore water of concrete changes. The color changes of the film influenced the transmission of light through the optical fibre. The colors of silica sol-gel film darken as if the pH value increases. This state causes the light to be refracted away from the fibre optic that renders the light detected on the other end (receiver) of fibre optic to decrease. The comparison with the measurements using electrochemical corrosion sensor shows that the constructed fibre optic corrosion sensor is capable to detect corrosion of the reinforcement in concrete. This was confirmed by visual inspection of the reinforcement when the concrete sample was broke open at the end of the experiment. Furthermore, the comparison with the measurements using pH meter shows that the fiber optic pH sensor is also capable to detect the changes of the pH in solution. However, the change of pH in mortar and concrete was not clearly distinguished